2015
DOI: 10.5194/hess-19-427-2015
|View full text |Cite
|
Sign up to set email alerts
|

An efficient workflow to accurately compute groundwater recharge for the study of rainfall-triggered deep-seated landslides, application to the Séchilienne unstable slope (western Alps)

Abstract: Abstract. Pore water pressure build-up by recharge of underground hydrosystems is one of the main triggering factors of deep-seated landslides. In most deep-seated landslides, pore water pressure data are not available since piezometers, if any, have a very short lifespan because of slope movements. As a consequence, indirect parameters, such as the calculated recharge, are the only data which enable understanding landslide hydrodynamic behaviour. However, in landslide studies, methods and recharge-area parame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 57 publications
(83 reference statements)
1
18
0
Order By: Relevance
“…Helmstetter and Garambois (2010) showed a weak but significant correlation between rainfall signals and rockfall micro-seismicity. Vallet et al (2015) showed that the Séchilienne displacement rates are better correlated to the recharge than to the precipitation, reinforcing the significant role of groundwater flow in the Séchilienne destabilization. Because of the mountainous location of the studied landslide, precipitation consists of rain and snow.…”
Section: Séchilienne Unstable Slopementioning
confidence: 91%
See 3 more Smart Citations
“…Helmstetter and Garambois (2010) showed a weak but significant correlation between rainfall signals and rockfall micro-seismicity. Vallet et al (2015) showed that the Séchilienne displacement rates are better correlated to the recharge than to the precipitation, reinforcing the significant role of groundwater flow in the Séchilienne destabilization. Because of the mountainous location of the studied landslide, precipitation consists of rain and snow.…”
Section: Séchilienne Unstable Slopementioning
confidence: 91%
“…To take into account the transit through the aquifer, the spring water δ 18 O signal was compared with the δ 18 O signal of a cumulated amount of precipitation that fell during the period between two consecutive spring sampling campaigns (about 3 months); thus, the isotopic signal of the rain collectors corresponds to the precipitation δ 18 O signal weighted by the 3-month rainfall amount. The 3-month period is based on the study of Vallet et al (2015) which shows that the best R 2 coefficient of determination between the cumulative groundwater recharge and the landslide velocity is obtained for periods from 68 to 132 days. As the landslide velocity is mainly controlled by the pore-water pressure, these periods can be considered as representative groundwater residence times.…”
Section: Seasonal Analysis and Spring Mean Recharge-area Elevationmentioning
confidence: 99%
See 2 more Smart Citations
“…The soil reservoir is a soil-water balance model which simulates a diffuse groundwater recharge through soil cover according to the workflow calculation proposed by Vallet et al (2015a). This computation requires a precipitation dataset and the estimation of the evapotranspiration ET ([L] dimension) and of parameters characterising the recharge area.…”
Section: Groundwater Model: Detrended Displacementmentioning
confidence: 99%